Sleep duration has a limited impact on the prevalence of menstrual irregularities in athletes: a cross-sectional study - Miyamoto, M.; Shibuya, K. (PeerJ, 2024)
Background This study aimed to investigate the relationship between the prevalence of menstrual irregularities, energy intake, and sleep deprivation among female athletes.